Pengaruh Financial Knowledge, Financial Technology, dan Financial Attitude terhadap Consumptive Behavior pada Generasi Z di Kecamatan Laweyan Kota Surakarta - Sendyka Duwi Firnando Putra; Annisa Indah Mutiasari; Destina Paningrum (Jurnal Kajian dan Penelitian Umum, 2026)
This study aims to examine the influence of financial knowledge, financial technology, and financial attitude on consumptive behavior among Generation Z in Laweyan District, Surakarta City. The rapid development of digital technology and the increasing accessibility of financial services have significantly influenced consumer behavior, particularly among Generation Z, which is highly engaged with technology in daily life. Therefore, it is important to understand the factors that affect consumptive behavior within this generation. This study employed a quantitative research approach using primary data collected directly from respondents through questionnaires. The sampling technique used was convenience sampling, with the criteria that respondents were members of Generation Z aged between 15 and 29 years and residing in Laweyan District, Surakarta City. A total of 394 respondents participated in the study. The data were analyzed using multiple linear regression to determine the effect of each independent variable on the dependent variable. The results indicate that financial knowledge, financial technology, and financial attitude each have a positive and significant effect on consumptive behavior. Furthermore, these three variables simultaneously have a significant influence on consumptive behavior among Generation Z in Laweyan District, Surakarta City.